Hukum Islam dan Kebudayaan: Studi Dialektika Hukum Islam dan Kearifan Lokal Masyarakat Nunukan - Rikawati; Ayziatur Rohmah; Revanina Tri Andini; M. Roby Wiraguna; Rezky Ananda (Syamil: Jurnal Pendidikan dan Pemikiran Islam, 2024)
This research aims to analyze the dialectics of Islamic law and local wisdom in the context of culture in Nunukan community. The study employs a qualitative research approach with an ethnographic design. Data were collected through in-depth interviews with informants, participant observation, and document analysis.The findings of this study reveal that Islamic law and local wisdom in Nunukan community have a complex and dynamic relationship. Islamic law has become an integral part of the community's culture, influencing various aspects of their lives, including social norms, values, and practices. However, local wisdom also plays a significant role in shaping the community's understanding and implementation of Islamic law.This research highlights the importance of considering the local context and cultural nuances in the implementation of Islamic law. The study demonstrates that the dialectics of Islamic law and local wisdom in Nunukan community can lead to a more harmonious and just way of life for the community. Furthermore, this research contributes to the understanding of the complex relationship between Islamic law and local culture, providing insights forpolicymakers, scholars, and practitioners.The study's findings also have implications for the development of Islamic law and its implementation in various cultural contexts. The research suggests that Islamic law should be understood and implemented in a way that takes into account the local culture and wisdom. This approach can help to promote a more inclusive and context-specific understanding of Islamic law, which can ultimately contribute to the well-being and prosperity of Muslim communities.